A Diagrammatic Proof Search Procedure as Part of a Formal Approach to Problem Solving - Batens, Diderik (Model Based Reasoning in Science and Engineering. Cognitive Science, Epistemology, Logic, 2006)
This paper aims at describing a goal-directed and diagrammatic method for proof search. The method (and one of the logics obtained by it) is particularly interesting in the context of formal problem solving. A typical property is that it consists of attempts to justify so-called bottom boxes by means of premise elements (diagrammatic elements obtained from premises) and logical elements. Premises are not preprocessed, whence most premises lead to a variety of premise elements.